CLINICOMORPHOLOGICAL CHARACTERISTICS OF THE WOUND PROCESS AT THE EARLY POSTOPERATIVE PERIOD AFTER RADICAL URANOSTAPHYLOPLASTY - Tkachenko, P.І.; Dolenko, О.B.; Lokhmatova, N.М.; Bilokon, S.О.; Dobroskok, V.О. (World of Medicine and Biology, 2018)
The purpose of the paper was to study the clinical situation and the morphological structure of the biopsy material of the hard palate mucoperiosteal grafts in children with the congenital cleft palate before surgery and at the early postoperative period after radical uranostaphyloplasty. The study of clinical characteristics and general somatic state of children with this pathology before operative intervention enables to reveal the marked anatomical and functional disorders. The study of the wound process at the early postoperative period after radical uranostaphyloplasty with the help of morphological structure of the biopsy material of the hard palate mucoperiosteal grafts enables to predict the degree of probability of the formation of dense scar and make individual plan of treatment-and-prophylactic and rehabilitation measures for this category of patients.
Keywords: children; congenital cleft palate; reparative regeneration